JAK inhibitors suppress t(8;21) fusion protein-induced leukemia - Lo, Miao-Chia (2013)
Oncogenic mutations in components of the JAK/STAT pathway, including those in cytokine receptors and JAKs, lead to increased activity of downstream signaling and are frequently found in leukemia and other hematological disorders. Thus, small-molecule inhibitors of this pathway have been the focus of targeted therapy in these hematological diseases. We previously showed that t(8;21) fusion protein AML1-ETO and its alternatively spliced variant AML1-ETO9a (AE9a) enhance the JAK/STAT pathway via down-regulation of CD45, a negative regulator of this pathway. To investigate the therapeutic potential of targeting JAK/STAT in t(8;21) leukemia, we examined the effects of a JAK2-selective inhibitor TG101209 and a JAK1/2-selective inhibitor INCB18424 on t(8;21) leukemia cells. TG101209 and INCB18424 inhibited proliferation and promoted apoptosis of these cells. Furthermore, TG101209 treatment in AE9a leukemia mice reduced tumor burden and significantly prolonged survival. TG101209 also significantly impaired the leukemia-initiating potential of AE9a leukemia cells in secondary recipient mice. These results demonstrate the potential therapeutic efficacy of JAK inhibitors in treating t(8;21) AML.